Assessment of Exposure to Chlorinated Organics through the Ingestion of Moose Meat for a Canadian First Nation Community - McAuley, Claire; Dersch, Ave; Kates, Lisa N.; Sowan, Darryel R.; Koppe, Bart; Ollson, Christopher A. (Frontiers in Environmental Science, 2016)
Moose is an important traditional food for members of the Swan River First Nation (SRFN), located in northern Alberta, Canada. As industrial development is encroaching on First Nations’ traditional territories in northern Alberta, community members are growing increasingly concerned for the sustainability and safety of their traditional foods. The Alberta Special Waste Treatment Centre (ASWTC) is an industrial incineration facility located in the core of SRFN’s traditional territory. An accidental release at the ASWTC in 1996 resulted in a significant discharge of polychlorinated biphenyls (PCBs) to the environment. In addition to this accident, the ongoing operation of the ASWTC is linked to routine low-level emissions of PCBs, polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs). Since the 1996 release, levels of PCBs and PCDD/Fs have been measured in wild game tissues and the provincial government has issued consumption advisories. This study was undertaken to provide answers to the community regarding food safety and was designed to address concerns regarding PCB and PCDD/F concentrations in moose tissues. Samples of moose muscle (n=15), liver (n=13) and kidney (n=14) were collected as part of regular food harvesting activities of the SRFN in the summer and fall of 2015 and generously shared by the SRFN hunters and harvesters to allow for their inclusion into the study. A risk assessment approach was used to evaluate the potential risks to human health using hazard quotients (HQ). All HQs were below the benchmark level of 0.2 for a single pathway exposure. The results show that PCB and PCDD/F concentrations in moose tissues were low and comparable to those of meats available in Canadian supermarkets. Based on results from this study, community exposure to PCBs and PCDD/Fs from the consumption of moose tissue is low and consumption may continue at quantities documented in regional studies.